2024
DOI: 10.1111/irv.13279
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection of Influenza A and B and Human OC43 Coronavirus in Normal Human Bronchial Epithelial Cells

JungHyun Kim,
Brady T. Hickerson,
Natalia A. Ilyushina

Abstract: BackgroundInfluenza viruses and seasonal coronaviruses are pathogens transmitted via an airborne route that can cause respiratory diseases in humans that have similar symptoms such as fever, cough, and pneumonia. These two viruses can infect similar human tissues, such as the respiratory tract and nasal, bronchial, and alveolar epithelial cells. Influenza virus and seasonal coronavirus coinfections are poorly understood.MethodsHere, we coinfected normal human bronchial epithelial (NHBE) cells with influenza A/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…As for the current study, one hypothesis is that the observed protective effect of exposure to coinfected index cases may be driven by this antagonistic relationship between rhinovirus and RSV/IAV, which could inhibit the transmission of these viruses of interest. Kim et al (2024) examined coinfections between influenza viruses and human OC43 coronavirus in normal human bronchial epithelial cells and found that while coinfection with OC43 did not affect replication of IAV or IBV, select cytokine/chemokine expression was increased in coinfected cells compared to singly infected cells. 26 A hypothesis for our other main finding is that coinfection among secondary cases with IAV or RSV plus another virus led to more symptomatic illness than infection with either of the viruses alone; because the HIVE study requires a standard ARI case definition for testing, these virus combinations would be detected more frequently if they more often resulted in illnesses that met the ARI definition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the current study, one hypothesis is that the observed protective effect of exposure to coinfected index cases may be driven by this antagonistic relationship between rhinovirus and RSV/IAV, which could inhibit the transmission of these viruses of interest. Kim et al (2024) examined coinfections between influenza viruses and human OC43 coronavirus in normal human bronchial epithelial cells and found that while coinfection with OC43 did not affect replication of IAV or IBV, select cytokine/chemokine expression was increased in coinfected cells compared to singly infected cells. 26 A hypothesis for our other main finding is that coinfection among secondary cases with IAV or RSV plus another virus led to more symptomatic illness than infection with either of the viruses alone; because the HIVE study requires a standard ARI case definition for testing, these virus combinations would be detected more frequently if they more often resulted in illnesses that met the ARI definition.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al (2024) examined coinfections between influenza viruses and human OC43 coronavirus in normal human bronchial epithelial cells and found that while coinfection with OC43 did not affect replication of IAV or IBV, select cytokine/chemokine expression was increased in coinfected cells compared to singly infected cells. 26 A hypothesis for our other main finding is that coinfection among secondary cases with IAV or RSV plus another virus led to more symptomatic illness than infection with either of the viruses alone; because the HIVE study requires a standard ARI case definition for testing, these virus combinations would be detected more frequently if they more often resulted in illnesses that met the ARI definition. Studies comparing disease severity between coinfections and single virus infections have had mixed results.…”
Section: Discussionmentioning
confidence: 99%